Grit and Gold : The Death Valley Jayhawkers of 1849 - Johnson, Jean, 1937- (Book collections on Project MUSE., 2018)
"The Death Valley Jayhawkers were a group of young gold seekers who blundered into Death Valley at Christmas 1849. They were an uncongealed group when they left western Illinois, although many had been friends at school in Galesburg, but while traveling along the Platte River Road toward the gold fields of California they held initiation rights that melded them into a jolly, but mutually supportive group of young men who saw their western trip as a spirited adventure. After leaving Salt Lake City to break a road south to the Pacific Coast that would eliminate crossing the snowy Sierra Nevada, they veered off the Old Spanish Trail in southern Utah to follow a old mountaineer's map portraying a bogus trail that claimed to cut months and hundreds of miles off their route to the gold country. Instead, as winter descended, they became totally lost in the mountains and dry valleys of southern Nevada and California and had to abandon everything but the shirts on their backs and the few oxen that became their pitiful meals on the hoof. This book weaves together the strands of their heroic, yet tragic story with the aid of William Lorton's superior 1894 diary of the trek from Illinois to southern Utah, the reminiscences of the Jayhawkers themselves, the keen memory of famed pioneer William Lewis Manly, and the almost daily diary of Sheldon Young (who became a Death Valley Jayhawker). It reveals the valor, determination, and guts characteristic of these early westerners; traits that have made America great. With adherence to accuracy and careful research, the author provides a lively but accurate true story of western grit, far more powerful than any fiction"--Provided by publisher.